Physicochemical Assessment of Branded and Generic Linezolid Injection from Different Pharmaceutical Manufacturers - Zhang, Su-hua; Wei, Shan-shan; Zhu, Zhen-yu; Chen, Ying; Cai, Hua-lin; Zhang, Bi-kui (Current Pharmaceutical Analysis, 2021)
Background: Up to date, generic linezolid injections produced by Chinese manufacturers were not widely used in clinics in China. Quality evaluation of linezolid injections produced in China is a prerequisite, which has rarely been performed. Objective: This study aimed to evaluate the quality of branded and generic injections from different manufacturers and to provide a basis for quality control. Methods: In this study, the content of linezolid, related impurities and enantiomer of linezolid were determined by high-performance liquid chromatography. The content of glucose was determined by the iodine method. The insoluble particles and visible and sub-visible particles were determined by light blockage and lamp test, respectively. Osmotic pressure was determined by the freezing point depression method. The standard solution control method was used to check the color of the injection. Linezolid injections from different manufacturers were evaluated uniformly. Results: No significant difference was found in the content of linezolid, glucose, related impurities, visible particles, insoluble particles, pH value, and solution color between branded and generic drugs from different manufacturers in China. Conclusion: The quality of samples from different manufacturers is consistent. Although the physicochemical similarity does not guarantee the bioequivalence of studied branded and generic linezolid injections, the results provide references for further bioequivalence study. Generic injections offer more affordable treatment options for patients with infections than expensive branded drugs.
Keywords: Linezolid